A model of stock prices leading earnings. Issue 7 (9th July 2018) - Lee, Jay Junghun
Abstract : Purpose: Prior literature suggests that stock prices lead earnings in reflecting value-relevant information because accounting income incorporates information discretely to satisfy recognition principles while stock prices incorporate it continuously. The purpose of this paper is to derive an analytical model that relates the time lag of earnings to the incremental informativeness of future anticipated earnings in equity prices after controlling for current realized earnings. Design/methodology/approach: This study models the extent to which forward-looking information about future earnings is capitalized into current stock returns. Specifically, this study derives an analytical future earnings response coefficient (FERC) model that regresses current stock returns on both current and future earnings surprises, and examines the properties of the regression coefficients on current earnings (i.e. current earnings response coefficient, CERC) and future earnings (i.e. FERC). Findings: The analytical FERC model shows that the pricing coefficient on future earnings (FERC) is positive in the presence of stock prices leading earnings. More importantly, the pricing coefficient on future earnings (FERC) increases with the recognition lag, but the pricing coefficient on current earnings (CERC) decreases with the lag. The results suggest that recognition principles that intend to enhance the reliability of earnings inadvertently lower the timeliness of earnings and, thus, shift the investors' demand for value-relevant information from current realized earnings to future anticipated earnings. Originality/value: This study makes two major contributions. First, it fills the gap between the lack of an analytical model and the abundance of empirical findings in previous FERC studies. As the recognition lag of earnings increases, stock investors shift the pricing weight on value-relevant information from current realized earnings to future anticipated earnings. Second, it provides support for the validity of the FERC model as an empirical model that examines the lack of earnings timeliness. As the timeliness of earnings relative to stock prices declines, the FERC increases but the CERC decreases.